RN First Assisting - 1997 Canadian Update - Groetzsch, Grace (Operating Room Nurses Association of Canada Journal, 1997)
Unlike the United States, Canada appears to have little formal history of nurses functioning in a RN first assistant (RNFA) role. On examination, however, perioperative nurses are first assisting in Canada daily, and more recently formally as RNFAS.